Applying Innovation Strategy and Its Effect on Competitive Advantage of Creative Industry: Spicy Culinary Subsector in Indonesia - Hamdani, Nizar Alam; Rawita, Rima Tita Vita (International Journal of Business, Economics, and Social Development, 2023)
The main issue of this study is the intense competition among business competitors both new business competitors and old business competitors which have controlled the Indonesian market. Besides, there has been an increasing number of SMEs that engage in culinary sector. However, many culinary sectors have still lack of quality. This study discusses the implementation of innovative strategies that affect the competitive advantage of creative industries in sub-sector of spicy culinary foods in Indonesia. Creative industry is an industry in which its main elements consist of creativity, expertise, and talents. These elements have greater potential in increasing the success by offering intellectual creation. The researchers used quantitative method. The samples of this study were 30 respondents as the business actors of SMES in spicy culinary food sub-sector in Indonesia. The technique of analyzing the data used was simple linear regression processing with SPSS version 25. Based on the result of the study, innovative strategies had positive and significant influence toward the competitive advantages. The results of this study support the previous studies that confirm if the business actors should have competitive advantage and have ability in creative and innovating thinking ability. This study proposes that SMES innovation strategy will greatly improve the performance and competitiveness of business. The further study is expected to observe other variables which are not studied in this study because it has been found 65% influence. However, this study has other practical benefits for the actors of SMEs in culinary sub-sector to improve the innovative strategies.